An empirical investigation of the use of limitations to freedom of religion or belief at the European Court of Human Rights - Pinto, Thiago Alves (Religion and human rights, 2020)
Most literature on freedom of religion or belief argues that there should be a high threshold for the imposition of limitations to the manifestation of the right. However, the practice of the European Court of Human Rights shows that the bar is much lower than academics suggest. This article explores this issue by analysing a plethora of cases and on the basis of interviews with lawyers connected to the Court. While the Court often considers the requirements of legality, legitimacy, and necessity, it does so briefly; focusing mostly on the analysis of proportionality and the margin of appreciation to the State in question. This approach makes the decisions exceedingly subjective and leads to little legal certainty in the area. Therefore, it is suggested that if the Court would analyse all criteria to impose limitations strictly, it could become more efficient while providing greater protection for persons to manifest their religion or belief.